2021
DOI: 10.1021/accountsmr.1c00149
|View full text |Cite
|
Sign up to set email alerts
|

Toward Efficient Charge Transport of Polymer-Based Organic Field-Effect Transistors: Molecular Design, Processing, and Functional Utilization

Abstract: Conspectus Polymer-based organic field-effect transistors (OFETs) have attracted great attention owing to their significantly improved performance and the recently emerged prospects for broad applications. The charge carrier mobility of polymer-based OFETs has been improved from 10–5 to more than 10 cm2 V–1 s–1 over the past three decades. With the carrier mobility close to or higher than that of amorphous silicon, the application fields of polymer-based OFETs have been extended from sensing to logic or drive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 60 publications
(117 reference statements)
0
23
0
Order By: Relevance
“…The pivotal factor however is that, in contrast to acenes, the chemical stability of HPs is excellent. Their carrier mobility is comparable with that of polycrystalline tetrathiafulvalene, larger than that of semiconducting polymers, 94 and much larger than that of regioisomeric thieno[3,4- b ]thiophenes. 2 They also favorably compare with competing materials as far as the ON/OFF voltage is concerned.…”
Section: Discussionmentioning
confidence: 95%
“…The pivotal factor however is that, in contrast to acenes, the chemical stability of HPs is excellent. Their carrier mobility is comparable with that of polycrystalline tetrathiafulvalene, larger than that of semiconducting polymers, 94 and much larger than that of regioisomeric thieno[3,4- b ]thiophenes. 2 They also favorably compare with competing materials as far as the ON/OFF voltage is concerned.…”
Section: Discussionmentioning
confidence: 95%
“…The transparent conductive oxide components normally used are indium tin oxide (ITO) and fluorine-doped tin oxide (FTO). As a result of material shortages, brittleness, and costs, conducting polymers are a potential alternative for TCO due to their excellent, simple nano/microscale self-assembly, abundancy, and mechanical flexibility [ 44 , 45 ].…”
Section: The First Generation Solar Cellsmentioning
confidence: 99%
“…The materials mentioned above have promising applications in photovoltaics, thin-film transistors, supercapacitors, gas sensors, LEDs, and wearable electronics. Furthermore, their charge transport mechanisms are not well understood yet; it has been reported that intra chain charge transport enhancement exists as a result of new electronegative groups in conjugated backbones and acceptor dimerization, promoting the carrier mobility and stability of semiconducting polymers [ 44 , 45 ].…”
Section: The First Generation Solar Cellsmentioning
confidence: 99%
See 2 more Smart Citations